A comparative study of the conceptual metaphors of time in Persian and English - Arsalan Golfam; Amir Ghorbanpour; Nader Mahdipour (Politeknik Negeri Bali, 2019)
From a cognitive perspective, metaphor is viewed as one of the important aspects and a fundamental part of the everyday use of language. Metaphor is generally defined as a means to talk about a more abstract conceptual domain in terms of another – more concrete – domain. The mapping between the two domains is expressed through some conceptual metaphors. This study is a comparative analysis of the conceptual metaphors of time in Persian and English. In doing so, different expressions of time in the two languages were categorized into the relevant conceptual metaphors, to be compared to find any similarities and differences in this respect. The expressions of the time were analyzed under eight different conceptual metaphors. It is revealed that the two languages show a very similar conceptualization of time-related expressions. Except for a few minor differences, both languages generally appear to use the same metaphoric structures to talk about time. The use of similar collocations with time words in most cases counts as evidence for the similarities between the two languages in their conceptualization of time.